REM sleep homeostasis in the absence of REM sleep: Effects of antidepressants - McCarthy, Andrew; Wafford, Keith; Shanks, Elaine; Ligocki, Marcin; Edgar, Dale M.; Dijk, Derk-Jan (Neuropharmacology, 2016)
Most antidepressants suppress rapid eye movement (REM) sleep, which is thought to be important to brain function, yet the resulting REM sleep restriction is well tolerated. This study investigated the impact of antidepressants with different mechanisms of action, such as selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants (TCA), on the regulation of REM sleep in rats. REM sleep was first demonstrated to be homeostatically regulated using 5, 8 and 10 h of REM-sleep specific restriction through EEG-triggered arousals, with an average of 91 ± 10% of lost REM sleep recovered following a 26–29 -hour recovery period. Acute treatment with the antidepressants paroxetine, citalopram and imipramine inhibited REM sleep by 84 ± 8, 84 ± 8 and 69 ± 9% respectively relative to vehicle control. The pharmacologically-induced REM sleep deficits by paroxetine and citalopram were not fully recovered, whereas, after imipramine the REM sleep deficit was fully compensated. Given the marked difference between REM sleep recovery following the administration of paroxetine, citalopram, imipramine and REM sleep restriction, the homeostatic response was further examined by pairing REM sleep specific restriction with the three antidepressants. Surprisingly, the physiologically-induced REM sleep deficits incurred prior to suppression of REM sleep by all antidepressants was consistently recovered. The data indicate that REM sleep homeostasis remains operative following subsequent treatment with antidepressants and is unaffected by additional pharmacological inhibition of REM sleep. •Selective serotonin re-uptake inhibitor antidepressants do not activate the REM sleep homeostat.•In contrast, the tricyclic antidepressant imipramine elicits a homeostatic response in REM sleep similar to that of REM sleep restriction.•The REM sleep homeostat remains active even in the presence of the pharmacological REM sleep inhibition antidepressants.